Hubungan Beban Pengasuhan Dan Kualitas Hidup Pada Perempuan Generasi Sandwich Di Kota Solok - Khalsum.YB, Namira Ummi; Rahayu, Sri Putri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Abstract The main problem in this thesis is that there are several housewives who have a low quality of life due to the high burden of caring for sick parents/in-laws and children who are still in elementary school. The purpose of this study was to determine the relationship between parenting burden and quality of life for sandwich generation women in Solok City. The research method used is a quantitative method with a correlational research type. The population in this study were 50 housewives who live together and play a role in caring for sick parents/in-laws and children who are still in elementary school. The research sample was 50 housewives who live together and play a role in caring for sick parents/in-laws and children who are still in elementary school. The author uses a Likert scale to obtain the required data on parenting burden and quality of life. Based on the results of the hypothesis testing, it shows that (rxy = -0.126), and with a significance of 0.383 (p <0.05) this means that the alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted. The results of this study indicate that there is no significant relationship between the burden of caregiving and quality of life, meaning that the high or low burden of care received by a mother cannot make her perceived quality of life low.Keywords: Cargiver Burden, Quality of Life, Women in the Sandwich Generation